Genetic, Maternal, and Environmental Risk Factors for Cryptorchidism: An Update - Barthold, Julia Spencer; Reinhardt, Susanne; Thorup, Jorgen (European Journal of Pediatric Surgery, 2016)
Unilateral or bilateral cryptorchidism is an isolated anomaly in the majority of cases, with evidence to date suggesting that it is a complex disorder resulting from interactions between genetic and environmental factors. Population, family, and limited genome-wide association data suggest moderate genetic risk, multiple susceptibility loci, and a role for the maternal environment. Epidemiologic studies have identified low birth weight or intrauterine growth retardation as factors most strongly associated with cryptorchidism, with additional evidence suggesting that maternal smoking and gestational diabetes increase risk. Animal studies have shown that the testis regulates its own descent by secretion of hormones that stimulate differentiation of the gubernaculum, and that endocrine-disrupting chemicals (EDCs) exhibit antiandrogenic and/or estrogenic activity that alters testicular function or gubernacular response to hormonal stimulation. However, we have yet to determine the degree to which EDCs contribute to cryptorchidism risk in humans, in part due to the varying methodology used in epidemiological and exposure studies. Large populations will be required to define the gene–environment interactions that predispose to cryptorchidism, in view of multiple small effect genetic susceptibility loci, ubiquitous exposure to mixtures of EDCs, and possible epigenetic effects. The present review provides an update of potential genetic and environmental risk factors for cryptorchidism, and future work required to better understand the etiology of this common and complex disease.
Keywords: cryptorchidism; genetic risk; endocrine-disrupting chemicals